Acceptance of HMIS by healthcare professionals of private sector hospitals of Pakistan - Ujan, Imran Anwar; Bhutto, A; Rind, M. M.; Suhaimi, Mohd Adam (2016)
As many of the high-end functions and services have been increasingly supported by the expansion of information technology (IT), it has become salient to explore any factor that may make individuals more prone to use it. When it comes to the user, technological and contextual features, there may be quite a difference in settings that are professional and those that involve day-to-day business. We collected the data from Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore and MAROOF International Hospital, Islamabad. A seven-point Likert-type scale from “strongly agree” to “strongly disagree” was used to measure all the items. Because of the chances of getting a response set on the items measuring a specific construct, the sentences were negatively worded for half number of items and were placed in a random alignment on the respective questionnaire. Investigation of the factors that may play an important role in making the professionals in healthcare department more prone to accept health information system was carried out in the present study. It was found that when the data from the healthcare professionals was compared with that of the user population taken in a previous research, the former group differed in a number of significant areas when it came to making decisions regarding technology acceptance.